Scaling up functional traits for ecosystem services with remote sensing: concepts and methods. Issue 13 (2nd June 2016) - Abelleira Martínez, Oscar J.; Fremier, Alexander K.; Günter, Sven; Ramos Bendaña, Zayra; Vierling, Lee; Galbraith, Sara M.; Bosque‐Pérez, Nilsa A.; Ordoñez, Jenny C.
Abstract: Ecosystem service‐based management requires an accurate understanding of how human modification influences ecosystem processes and these relationships are most accurate when based on functional traits. Although trait variation is typically sampled at local scales, remote sensing methods can facilitate scaling up trait variation to regional scales needed for ecosystem service management. We review concepts and methods for scaling up plant and animal functional traits from local to regional spatial scales with the goal of assessing impacts of human modification on ecosystem processes and services. We focus our objectives on considerations and approaches for (1) conducting local plot‐level sampling of trait variation and (2) scaling up trait variation to regional spatial scales using remotely sensed data. We show that sampling methods for scaling up traits need to account for the modification of trait variation due to land cover change and species introductions. Sampling intraspecific variation, stratification by land cover type or landscape context, or inference of traits from published sources may be necessary depending on the traits of interest. Passive and active remote sensing are useful for mapping plant phenological, chemical, and structural traits. Combining these methods can significantly improve their capacity for mapping plant trait variation. These methods can also be used to map landscape and vegetation structure in order to infer animal trait variation. Due to high context dependency, relationships between trait variation and remotely sensed data are not directly transferable across regions. We end our review with a brief synthesis of issues to consider and outlook for the development of these approaches. Research that relates typical functional trait metrics, such as the community‐weighted mean, with remote sensing data and that relates variation in traits that cannot be remotely sensed to other proxies is needed. Our review narrows the gap between functional trait and remote sensing methods for ecosystem service management. Abstract : The use of functional traits to inform ecosystem service management requires the scaling‐up of trait variation from local to regional scales. In this study, we review (1) the current conceptual understanding of trait‐based approaches for sampling trait variation across spatial scales, and (2) available remote sensing methods that facilitate the scaling‐up of trait variation from local to regional scales. Our review highlights research needs to improve the utility of remote sensing methods for capturing the modification of functional trait variation due to anthropogenic land cover and climate change.